Barriers to seeking timely treatment for severe childhood pneumonia in rural Bangladesh. Issue 5 (15th September 2021) - Chowdhury, Kamal Ibne Amin; Jabeen, Ishrat; Rahman, Mahfuzur; Faruque, Abu Syed Golam; Alam, Nur H; Ali, Shahjahan; Ahmed, Tahmeed; Fuchs, George J; Duke, Trevor; Gyr, Niklaus; Sarma, Haribondhu
Abstract : Objective: Delays in seeking medical attention for childhood pneumonia may lead to increased morbidity and mortality. This study aimed at identifying the drivers of delayed seeking of treatment for severe childhood pneumonia in rural Bangladesh. Methods: We conducted a formative study from June to September 2015 in one northern district of Bangladesh. In-depth interviews were conducted with 20 rural mothers of children under 5 years with moderate or severe pneumonia. We analysed the data thematically. Results: We found that mothers often failed to assess severity of pneumonia accurately due to lack of knowledge or misperception about symptoms of pneumonia. Several factors delayed timely steps that could lead to initiation of appropriate treatment. They included time lost in consultation with non-formal practitioners, social norms that required mothers to seek permission from male household heads (eg, husbands) before they could seek healthcare for their children, avoiding community-based public health centres due to their irregular schedules, lack of medical supplies, shortage of hospital beds and long distance of secondary or tertiary hospitals from households. Financial hardships and inability to identify a substitute caregiver for other children at home while the mother accompanied the sick child in hospital were other factors. Conclusions: This study identified key social, economic and infrastructural factors that lead to delayed treatment for childhood pneumonia in the study district in rural Bangladesh. Interventions that inform mothers and empower women in the decision to seek healthcare, as well as improvement of infrastructure at the facility level could lead to improved behaviour in seeking and getting treatment of childhood pneumonia in rural Bangladesh. Abstract : Lower respiratory illness remains the largest cause of mortality for children under 5 worldwide. Early intervention and care can be profoundly lifesaving, but significant barriers to seeking care remain. In this qualitative study, several are identified among Bangladeshi mothers.